Afghanistan : Balancing Social and Security Spending in the Context of Shrinking Resource Envelope - Aslam, Aqib (IMF Working Papers; Working Paper ;, 2013)
For Afghanistan, the dual prospect of declining donor support and high ongoing security spending over the medium term keeps the government budget tight. This paper uses a general equilibrium model to capture the security-development tradeoff facing the government in its effort to rehabilitate macroeconomic stability and welfare. In particular, it considers strategic policy options for counteracting and minimizing the negative macroeconomic impact of possible aid and revenue shortfalls. We find that the mobilization of domestic revenues through changes in tax policy is the preferred policy response for Afghan central government. Such a response helps to place its finances on a sustainable path and preserve most of the growth potential. Cutting expenditures balances public finances, but causes the economy to permanently shrink. Debt financing helps to preserve much of the economy size but can jeopardize the sustainability of public finances.